Control of Perennial Grasses in Forestlands with Application of Herbicides - Ray, Bibbas; Agarwala, S. B. D.; Fridrickson, C. J. (Indian Forester, 1975)
Two split applications of Dalapon at 5.5 kg per hectare (active ingredient) at an interval of 3 to 4 weeks in early spring gave adequate control of perennial grasses (Demostachya bipinnata and Veliveria zizanoides) in forestland. Hyvar X (Bromacil) applied at 17 kg per hectare (active ingredient) effected complete control of all above ground vegetation for the season. For long term benefit, the application of Dalapon may be economical for grass control compared to conventional cultivation methods.